The Influence of Behavior Biases on Investment Decisions Is Moderate by Financial Literacy Among Government Employees at The Republic of Indonesia's BPK - Virnalici, Virnalici; Ulupui, Igka; Dharmawan Buchdadi, Agung (Lafadz Jaya Publisher, 2024)
The purpose of the study is to examine the impact of behavioural biases (herding, mental accounting, and regret averson) on investment decisions. The authors further examine the moderation effect of financial literacy in the relationship between behaviour biases and investment decisions. The study considered a cross-sectional research design. For this survey, the data have been collected through a structured questionnaire from 215 government officials of BPK RI. To analyse the validity and reliability, the Pearson correlation and Cronbach’s alpha test have been taken into account respectively. For testing the hypothesis, hierarchical regression analysis has been used in the study. The results of the study reveal that research results also show that bias herding, mental accounting, and regrets on investment decisions have a positive and significant influence. Meanwhile, financial literacy on investment decisions has a negative and significant influence. Furthermore, herding bias is moderated by financial literacy on investment decisions and has a positive and significant influence. Meanwhile, mental accounting bias and regret aversion are moderated by financial literacy on investment decisions and have a negative and significant influence. Based on this present research finding, the study is more productive for the government officials and policymakers at the time of making an investment portfolio for the government officials based on their behavioural biases. The study recommends that investors need training programmes, workshops and seminars that enhance financial literacy and financial knowledge of government officials which helps them to overcome behavioural biases while making an investment decision. The current study aims to explore whether several behavioural biases can affect investment decisions. Moreover, the authors would like to examine whether these associations are moderated by financial literacy. In this sense, financial literacy might also play a substantial part in the prediction of investments. The current study might be of the first study that examines the moderation effect financial literacy amongst male and female investors.